Study of Chemical Composition and Antibacterial Activity of Rosmarinus officinals and Eucalyptus spathulata Hook Extracts - Rasheed , Emad (University of Thi-Qar Journal of Science, 2010)
The chemical composition and antibacterial activity of Rosmarinus officinalis and Eucalyptus spathualata leaves extracts, which were prepared by steam distillation and extraction by ethanol 95% for two hours were studied against the Staphylococcus aureus and Pseudomonas areuginosa by using agar well diffusion method. The results showed that the alcoholic extracts gave a percentage of dry weight of crude substance of Rosemary leaves was 31% and 40.25% for eucalyptus leaves. The results also, showed that the primary chemical composition of rosemary leaves extract contains alkaliods, flavonoids, resins, phenol glycosides, saponins, tannins, terpene, cineol and α-pinene. The chemical constituents of eucalyptus leaves extract include alkaloids,flavonoids, glycosides, phenol, coumarins, saponins, tannins, steroids and terpene. The antibacterial activity showed that both leaves extracts were effective against both bacteria. The minimum inhibitory concentration (MICs) of rosemary extract were 0.5 mg/ml for S. aureus and 1.0 mg/mlfor P. areuginosa and the MICs of eucalyptus leaves extract were 0.25 mg/ml for S. aureus and 1.0 mg/ml for P. areuginosa .